Doping Lanthanide Nanocrystals With Non-lanthanide Ions to Simultaneously Enhance Up- and Down-Conversion Luminescence - Li, Yingying; Liu, Chunyan; Zhang, Peisen; Huang, Jiayi; Ning, Haoran; Xiao, Peng; Hou, Yi; Jing, Lihong; Gao, Mingyuan (Frontiers in Chemistry, 2020)
The rare-earth nanocrystals containing Er3+ emitters offer very promising tools for imaging applications, as they can not only exhibit up-conversion luminescence but also down-conversion luminescence in the second near-infrared window (NIR II). Doping non-lanthanide cations into host matrix was demonstrated to be an effective measure for improving the luminescence efficiency of Er3+ ions, while still awaiting in-depth investigations on the effects of dopants especially those with high valence states on the optical properties of lanthanide nanocrystals. To address this issue, tetravalent Zr4+ doped hexagonal NaGdF4:Yb,Er nanocrystals were prepared, and the enhancement effects of the Zr4+ doping level on both up-conversion luminescence in the visible window and down-conversion luminescence in NIR II window were investigated, with steady-state and transient luminescence spectroscopies. The key role of the local crystal field distortions around Er3+ emitters was elucidated in combination with the results based on both of Zr4+ and its lower valence counterparts, e.g., Sc3+, Mg2+, Mn2+. Univalent ions such as Li+ was utilized to substitute Na+ ion rather than Gd3+, and the synergistic effects of Zr4+ and Li+ ions by co-doping them into NaGdF4:Yb,Er nanocrystals were investigated towards optimal enhancement. Upon optimization, the up-conversion emission of co-doped NaGdF4:Yb,Er nanocrystals were enhanced by more than one order of magnitude compared with undoped nanocrystals. The current studies thus demonstrate that the local crystal field surrounding emitters is an effective parameter for manipulating the luminescence of lanthanide emitters.